PERBEDAAN PERBANDINGAN LARUTAN CELUP (VLOT) TERHADAP HASIL PENCELUPAN BAHAN SUTRA MENGGUNAKAN EKSTRAK KELOPAK BUNGA ROSELLA (HIBISCUS SABDARIFFA L) DENGAN MORDAN TAWAS (AL2(SO4)3) - Syafitri, Rika; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to reveal the color (hue), dark light color (value) and flatness, and wash resilience. This study was an experimental study. The type of data is primary data sourced from the 15 panelists. The object is dipped silk fabric with extracts of rosella flower petals with alum mordant. Where do the data analysis techniques with engineering analysis of varianceone (one-way ANOVA). From the comparison of the dye solution (vlot) 1:10 produce powder blue color, light and dark colors (Value) is at katerori bright, flatness is in the category average and for washing resistance is at good enough category. Whereas in comparison dyebath (Vlot) 1:20 and 1:40 to produce color light blue, light dark color (Value) is at katerori quite bright, flatness is in the category average, and for washing resistance is at good enough category. Results of hypothesis testing showed the name of the color (F arithmetic (8.933)> F table (3.22) and dark colors (Fhitung (35.467)> F table (3.22) there are significant differences. As for the flatness of color (F count (2.907)> F table (3.22) and wash resistance (F arithmetic (0.214) <F table (3.22) there is no significant difference. Keywords: Comparison of dye liquor (Vlot), results of Immersion, extract rosella flower petals